2015
DOI: 10.1002/pon.3778
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer‐related lymphedema and sexual experiences: a mixed‐method comparison study

Abstract: Recommendations for healthcare professionals, social workers, and marriage and family therapists are offered with the aim of assisting women with breast cancer-related lymphedema and their sexual partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(53 reference statements)
0
10
0
1
Order By: Relevance
“…Self-care for lymphedema symptoms refers to activities that individuals initiate and perform for themselves, without professionally administered treatments (e.g., by lymphedema therapists or nurses) ( Fu, 2010b , Ridner et al, 2012 ). Since the experience of lymphedema symptoms leads to poor QOL (performance outcome) in breast cancer survivors ( Fu et al, 2013 , Passik and McDonald, 1998 , Ridner, 2005 , Radina et al, 2015 ) and the increased limb volume and lymph fluid level (physiological outcomes) ( Cormier et al, 2009 , Fu et al, 2015a ), the goal of self-care is to prevent, relieve or decrease lymphedema symptom occurrence (i.e. number and severity of symptoms) so as to improve QOL and achieve optimal limb volume and lymph fluid level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-care for lymphedema symptoms refers to activities that individuals initiate and perform for themselves, without professionally administered treatments (e.g., by lymphedema therapists or nurses) ( Fu, 2010b , Ridner et al, 2012 ). Since the experience of lymphedema symptoms leads to poor QOL (performance outcome) in breast cancer survivors ( Fu et al, 2013 , Passik and McDonald, 1998 , Ridner, 2005 , Radina et al, 2015 ) and the increased limb volume and lymph fluid level (physiological outcomes) ( Cormier et al, 2009 , Fu et al, 2015a ), the goal of self-care is to prevent, relieve or decrease lymphedema symptom occurrence (i.e. number and severity of symptoms) so as to improve QOL and achieve optimal limb volume and lymph fluid level.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of patient-centered care for lymphedema symptoms has been evidenced by > 40% of breast cancer survivors never receiving information about lymphedema ( Fu et al, 2010a , Ridner et al, 2011a ). In spite of the growing body of evidence linking the experience of lymphedema symptoms to poor QOL which are critical to cancer survivorship ( Fu et al, 2013 , Passik and McDonald, 1998 , Ridner, 2005 , Radina et al, 2015 ), the experience of lymphedema symptoms is often not valued as an essential factor that impact breast cancer survivors' QOL, therefore is not considered essential for patient-centered outcome, assessment or inclusion in clinical research and practice. In addition, oftentimes clinicians' intentions for helping breast cancer survivors are impeded by lack of information about lymphedema symptoms, lack of guidance in how to assess lymphedema symptoms, and lack of standardized and effective interventions for managing lymphedema symptoms ( Fu et al, 2012 , Ryan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, negative social impact such as isolation, social withdrawal, and decreased QOL have been reported (Panobianco et al, 2014; Pusic et al, 2013; Shigaki et al, 2013). Loss of sexual intimacy has also been noted (Panobianco et al, 2014; Radina, Fu, Horstman, & Kang, 2015; Thomas et al, 2015; Winch et al, 2015). In their systematic review of 23 studies, Fu et al (2013) noted the psychological affect physical and psychological factors have on women dealing with BCRL.…”
Section: Bcrl Impactmentioning
confidence: 99%
“…We note recent studies focusing on BCRL economic burden and return-to-work issues [41, 42•, 43-47, 48•], and few studies addressing sexuality concerns [27][28][29], and body image and self-esteem [23][24][25][26]. An interesting finding in this review is the number of reports identifying continued challenges among those with BCRL in receiving education about BCRL and their perceptions about health care providers' abilities to meet their psychosocial care needs [50-56, 57•].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, interest in sexual activity improved gradually during the year after surgery; however, moderate or severe problems with sexual interest and activity persisted over time due to upper limb dysfunction secondary to BCRL [27]. Compared with women without BCRL (n = 109), women with BCRL (n = 243) reported struggles with compression garments and sexual intimacy, negative feelings involving the breast and arm, and feelings of decreased sexual desire [28]. A study examining the impact of BCRL on sexual functioning reported that a supportive partner was essential in assisting women to overcome sexual issues caused by severe swelling and/or body image concerns (N = 17) [29].…”
Section: Psychological Health Factorsmentioning
confidence: 99%